2006
DOI: 10.1080/13548500500344255
|View full text |Cite
|
Sign up to set email alerts
|

Depressive affect among health care seekers: How it is related to attachment style, emotional disclosure, and health complaints

Abstract: The present cross-sectional questionnaire survey investigated depressive affect among persons visiting their general practitioner (GP). It examined the impact of a number of factors likely to be associated with depressive affect, including demographic variables, severity of medical condition, and personal factors such as ease in disclosing personal information, and attachment style. Results showed that among the sample of patients (N = 198) visiting their GP, depressive affect was generally quite high. In part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…To explain this, they assume individuals who are high in avoidant attachment tend to suppress their emotions and do not seek social support when they are distressed (Mikulincer et al, 2003). Also, the findings of Zech et al (2006) showed that avoidant attachment was not associated with emotion disclosure and depressive affect. However, the authors explained that while there is a growing independency in avoidant individuals, they would not accept negative feelings.…”
Section: Attachment Emotion Regulation and Mental Disordersmentioning
confidence: 91%
See 1 more Smart Citation
“…To explain this, they assume individuals who are high in avoidant attachment tend to suppress their emotions and do not seek social support when they are distressed (Mikulincer et al, 2003). Also, the findings of Zech et al (2006) showed that avoidant attachment was not associated with emotion disclosure and depressive affect. However, the authors explained that while there is a growing independency in avoidant individuals, they would not accept negative feelings.…”
Section: Attachment Emotion Regulation and Mental Disordersmentioning
confidence: 91%
“…In another study concerning emotional disclosure and mental disease, Zech et al (2006) investigated depressive affect in 198 patients visiting a general practitioner (GP) to find whether it is related to attachment, emotional disclosure and health complaints. Individuals with anxious attachment showed more depressive affect (b= .30, p < .001) and they disclose their emotion (r= .31).…”
Section: Depression and Anxiety Disordersmentioning
confidence: 99%
“…Thus, we examined whether relationship status moderated the correlation between adult attachment and mental health. That said, cohabitation with an unmarried romantic partner and marriage may have similar psychological effects, and many studies tend to report the proportion of married or cohabiting participants in total (Dagnino et al, 2017; Espeleta et al, 2017; Falgares et al, 2019; Kohlhoff & Barnett, 2013; Marques et al, 2018; Nielsen et al, 2017; O’Neill & Murray, 2016; Reizer, 2015; Segel-Karpas et al, 2013; Zech et al, 2006). Thus, we operationalized relationship status as cohabiting and/or married versus not.…”
Section: Adult Attachmentmentioning
confidence: 99%
“…Anxious attachment , which is associated with exaggeration of distress and constant help seeking (Mikulincer & Shaver, 2007), was positively related to symptom reporting in both undergraduates (Feeney & Ryan, 1994) and women in a health maintenance organization (Ciechanowski et al, 2002). Patients in the Netherlands visiting their general practitioner for psychological problems had higher scores in anxious attachment, whereas those visiting for physical health problems had higher avoidant attachment (Zech, de Ree, Berenschot, & Stroebe, 2006).…”
mentioning
confidence: 99%